Pelatihan dan Implementasi Smart Sewing Machine (SSM) Guna Peningkatan Efisiensi Produksi dan Pengurangan Waste Kain pada Komunitas Penjahit Kriya Wanita - Syahri, Riduan; Edowinsyah; Alfis Arif (LOSARI DIGITAL, 2025)
Textile waste is one of the largest contributors to solid waste, requiring innovative handling. Community partners, especially tailors and recycling activists, often face challenges in production efficiency, waste management, and digital market access. This community service aims to address these challenges through comprehensive training and technology utilization. The method employed involves training, mentoring, and hands-on practice focusing on three main aspects: 1) Textile Waste Utilization using creative upcycling techniques, 2) Simple Business Management to enhance business sustainability, and 3) Digital Marketing for recycled products. The main innovation in this activity is the introduction and practice of using SSM (Smart Sewing Machine), which can significantly increase the speed and precision of recycled product production. The results show a significant improvement in partners' technical skills in processing textile waste into economically valuable products, increased understanding of financial and inventory management, and expanded market access through digital platforms. This training successfully transformed the perception of textile waste into a sustainable business opportunity. It is hoped that this activity can serve as a model for both waste reduction and sustainable income generation for the community